Organizational Culture and Employee Job Satisfaction - A Case Study of an Automobile Dealer in the City of Belgaum, Karnataka, India - Kulkarni, Praveen M.; Kumar, D. N. S.; Janakiram, B. (Prabandhan: Indian Journal of Management, 2009)
This study was undertaken to investigate the links between organizational culture and employee job satisfaction in an automobile concern in the city of Belgaum, Karnataka, India. Organizational Culture profile (Udai Pareek, 2002) and employee job satisfaction (Paul E Spector, 1997) instruments were administered to draw the understand the impact of organizational culture on employee job satisfaction. The results of statistical treatments allowed the researchers to conclude that there are significant differences in organizational culture and job satisfaction among the employees at the study organization.